PENERAPAN RESTORATIVE JUSTICE TERHADAP PELAKU PENYEBARAN BERITA BOHONG TERKAIT PANDEMI COVID-19 DI BARESKRIM POLRI - Riyanto (2022)
During the COVID-19 pandemic, the spread of fake news (Hoax) through social media has recently been frequently used by irresponsible persons to create noise and panic among the public. However, if all perpetrators of spreading hoaxes are punished, it will cause other new problems such as over capacity, increasing case arrears, the number of law enforcers who are not in balance with developments because most of the Indonesian criminal justice system always ends up in prison. The purpose of this study is to carefully examine and analyze the Application of Restorative Justice to Perpetrators of Disseminating False News Related to the COVID-19 Pandemic at the Indonesian National Police BARESKRIM and Obstacles in the Implementation of Restorative Justice against Perpetrators of Disseminating False News Related to the COVID-19 Pandemic in the Indonesian National Police BARESKRIM. The legal research method used is a normative juridical legal research method by conducting research on library materials and using a statutory approach and a case approach. The results of the study are that in its application Restorative Justice can be carried out while still paying attention to some of the provisions and conditions stipulated in the regulations and still paying attention to several criteria in this case the crime of spreading false news and obstacles in the application of Restorative Justice are none other than Polri investigators who often experience hesitancy to use the Restorative Justice approach and the negative response from the community towards peaceful settlement efforts, in this case using the Restorative Justice approach, as well as how big the impact of the criminal act of spreading false news which becomes a reference for whether or not a criminal acts can be resolved using a Restorative Justice approach.